The Efforts Of Social Studies Teachers To Enhance Student Discipline Through An Independent Approach At MTsN 2 Deli Serdang - Br Tarigan, Giva Nisa Pangesti; Ponidi, Ponidi (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the role of teachers in promoting student discipline through various teaching strategies and educational approaches. Discipline is a fundamental element of educational success; thus, it is essential to understand how teachers can serve as role models, mentors, and motivators in shaping students’ disciplinary character. A qualitative approach was employed in this study, utilizing literature review techniques and descriptive analysis. Data were gathered from diverse sources, including academic journals, scholarly books, and prior research relevant to the topic. The findings indicate that teachers can effectively enhance student discipline by applying positive reinforcement, fostering a conducive learning environment, and implementing clear and consistent rules. Moreover, involving students in the formulation of classroom regulations and adopting a democratic approach in classroom management have proven effective in instilling a sense of responsibility and self-discipline. Engaging and varied teaching methods also contribute to the natural development of discipline, reducing the need for coercion. In conclusion, the teacher's role in cultivating discipline extends beyond rule enforcement; it encompasses exemplary behavior, motivational guidance, and the creation of a supportive learning atmosphere. When implemented with the right strategies, discipline becomes internalized among students, positively influencing their academic performance and character development in the long term.